Effects of a multifaceted medication reconciliation quality improvement intervention on patient safety: final results of the MARQUIS study. Issue 12 (20th August 2018) - Schnipper, Jeffrey L; Mixon, Amanda; Stein, Jason; Wetterneck, Tosha B; Kaboli, Peter J; Mueller, Stephanie; Labonville, Stephanie; Minahan, Jacquelyn A; Burdick, Elisabeth; Orav, Endel John; Goldstein, Jenna; Nolido, Nyryan V; et al.
Abstract : Background: Unintentional discrepancies across care settings are a common form of medication error and can contribute to patient harm. Medication reconciliation can reduce discrepancies; however, effective implementation in real-world settings is challenging. Methods: We conducted a pragmatic quality improvement (QI) study at five US hospitals, two of which included concurrent controls. The intervention consisted of local implementation of medication reconciliation best practices, utilising an evidence-based toolkit with 11 intervention components. Trained QI mentors conducted monthly site phone calls and two site visits during the intervention, which lasted from December 2011 through June 2014. The primary outcome was number of potentially harmful unintentional medication discrepancies per patient; secondary outcome was total discrepancies regardless of potential for harm. Time series analysis used multivariable Poisson regression. Results: Across five sites, 1648 patients were sampled: 613 during baseline and 1035 during the implementation period. Overall, potentially harmful discrepancies did not decrease over time beyond baseline temporal trends, adjusted incidence rate ratio (IRR) 0.97 per month (95% CI 0.86 to 1.08), p=0.53. The intervention was associated with a reduction in total medication discrepancies, IRR 0.92 per month (95% CI 0.87 to 0.97), p=0.002. Of the four sites that implemented interventions, three had reductions in potentially harmful discrepancies. The fourth site, which implemented interventions and installed a new electronic health record (EHR), saw an increase in discrepancies, as did the fifth site, which did not implement any interventions but also installed a new EHR. Conclusions: Mentored implementation of a multifaceted medication reconciliation QI initiative was associated with a reduction in total, but not potentially harmful, medication discrepancies. The effect of EHR implementation on medication discrepancies warrants further study. Trial registration number: NCT01337063 .